Study of thermal material properties for Ta- and Al-substituted Li7La3Zr2O12 (LLZO) solid-state electrolyte in dependency of temperature and grain size. Issue 22 (25th May 2022) - Neises, Julian; Scheld, Walter Sebastian; Seok, Ah-Ram; Lobe, Sandra; Finsterbusch, Martin; Uhlenbruck, Sven; Schmechel, Roland; Benson, Niels
Abstract : Investigating thermal material properties such as thermal conductivity ( κ ), specific heat capacity ( C p ) and decomposition temperature of Ta- and Al-substituted solid state electrolyte Li7 La3 Zr2 O12 (LLZO) in dependency of temperature and grain size. Abstract : Solid-state electrolytes such as tantalum (Ta)- and aluminum (Al)-substituted Li7 La3 Zr2 O12 (LLZO) are seen as the key component for the next generation of mainstream battery technology. However, this development often lacks specific information on decisive material parameters. Therefore, this work experimentally investigates the thermal material parameters such as the thermal conductivity ( κ ) and the specific heat capacity ( C p ) of LLZO between room temperature and 1225 K using laser flash analysis (LFA) and differential scanning calorimetry (DSC). The DSC measurements reveal a C p of 0.55–0.80 J g −1 K −1 . Furthermore, a decomposition of the cubic LLZO phase to pyrochlore La2 Zr2 O7 is detected between 1500 K and 1750 K, which is substantiated by Raman- and SEM-analysis. The impact of the grain size on κ is also considered, as the Al-substitution leads to the formation of significantly larger grain sizes compared to a Ta-substitution. The LFA measurements yield a relatively constant κ between 1.45–1.55 W m −1 K −1 for both materials and grain sizes, which is the consequence of a phonon mean free path in the range of the interatomic distance of the LLZO crystal. This implies that phonon scattering at grain boundaries is negligible and the main scattering occurs at inhomogeneities in the crystal lattice.